Z 49 lat pracy duszpasterskiej 14 lat w Szadku – ks. Edward Lidtke - Rulka, Kazimierz (Biuletyn Szadkowski, 2009)
Father Edward Lidtke (1879–1951), before becoming a parish-priest in Szadek, had already spent 32 years in pastoral work, first as curate and prefect in Pabianice (1902–1907) and Kalisz (1907–1914), and them as parish-priest in Kłobia (1914–1920), Chełmce (1920–1924), Grodziesze Wielkie (1924–1926), Dembe (1926-1933), Warta (1933–1934). Five and a half years of his 14-year office in Szadek (1934–1948) fell on World War II and German occupation in Poland. In the pre-war period he strove to provide ministerial services to all parishioners and religions education to all children and young people. He also took great care of the parish church – had it painted inside and had new Stations of the Cross fitted in. He also looked after the financial matters of the parish. He remained in the parish during the war but had to sign the German nationality list. He could not perform his religions duties officially, only conspiratorial ministration was possible. After the war he undertook work on revival of religious life in the parish, but his wartime act made it difficult. In response to repeated suggestions from the bishop of Włocławek he resigned from this parish in 1948 and moved to Iwanowice, where he was the parish-priest until the end of his life.